2012
DOI: 10.1089/end.2012.0036
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Blockers Impact Stent-Related Symptoms: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Alfuzosin 10 mg once daily in patients with a Double-J stent significantly decreases the bothersome urinary symptoms, besides decreasing significantly the pain associated with the stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 18 publications
2
36
0
Order By: Relevance
“…In terms of the results of statistical analysis, significant differences in IPSS voiding symptom sub-scores (MD, -2.66; 95% CI, -4.36 to -0.96) were detected; however, no significant differences in IPSS storage symptom sub-scores (MD, -0.93; 95% CI, -2.28 to 0.43) were detected (Table IV). The pooled USSQ urinary symptoms score data (MD, -5.84; 95% CI, -9.35 to-2.33) for seven studies (13,16,(22)(23)(24)(25)30) demonstrated that α 1 -blockers administration significantly reduced USS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of the results of statistical analysis, significant differences in IPSS voiding symptom sub-scores (MD, -2.66; 95% CI, -4.36 to -0.96) were detected; however, no significant differences in IPSS storage symptom sub-scores (MD, -0.93; 95% CI, -2.28 to 0.43) were detected (Table IV). The pooled USSQ urinary symptoms score data (MD, -5.84; 95% CI, -9.35 to-2.33) for seven studies (13,16,(22)(23)(24)(25)30) demonstrated that α 1 -blockers administration significantly reduced USS.…”
Section: Resultsmentioning
confidence: 99%
“…A Russian article published in Urologiia met the inclusion criteria according to the English abstract in PubMed; however it was subsequently excluded, since the full text could not be located (21). A total of 14 RCTs including 1,075 patients were included in the present meta-analysis (13,15,16,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations